Small intestinal bacterial overgrowth and metabolic dysfunction-associated steatotic liver disease - Wang, Ziteng; Tan, Wentao; Huang, Jiali; Li, Qian; Wang, Jing; Su, Hui; Guo, Chunmei; Liu, Hong (Frontiers in Nutrition, 2024)
Small intestinal bacterial overgrowth (SIBO), characterized by alterations in both the type and quantity of bacteria in the small intestine, leads to impaired intestinal digestion and absorption that can cause a range of clinical symptoms. Recent studies have identified significant changes in the composition of the small intestinal microbiota and metabolomic profiles of patients with metabolic dysfunction-associated steatotic liver disease (MASLD). This study systematically reviewed and synthesized the available data to explore the association between SIBO and MASLD. Comprehensive literature searches of the Embase, PubMed, Web of Science, Ovid, and Cochrane databases were conducted. Article quality screening was performed using the Newcastle-Ottawa Quality Assessment Scale. Cross-sectional, cohort, and case–control studies were included. A total of 7,200 articles were initially screened, of which 14 were ultimately included for analysis. Individuals with SIBO in both the MASLD and non-MASLD groups were extracted and a chi-square test was performed to calculate the odds ratio (OR) and 95% confidence interval (CI). The I2 index was used to measure heterogeneity. For heterogeneity >50%, a random effects model was used. There was a clear association between SIBO and MASLD (OR = 3.09; 95% CI 2.09–4.59, I2 = 66%, p < 0.0001). Subgroup analyses by MASLD stage showed that the probability of SIBO positivity increased with MASLD lesion severity. After stratifying by the diagnostic methods for SIBO and MASLD, the meta-analysis results suggest a reduction in inter-group heterogeneity. For the MASLD subgroup diagnosed via liver biopsy, the OR was 4.89. A subgroup analysis of four studies that included intestinal permeability testing revealed an OR of 3.86 (95% CI: 1.80–8.28, I2 = 9%, p = 0.0005). A meta-regression analyses revealed that both race and regional development level significantly influenced the relationship between SIBO and MASLD (p = 0.010, p = 0.047). In conclusion, this meta-analyses provides strong evidence that SIBO may contribute to the development and progression of MASLD. The strongest associations were observed between lactulose breath testing, gut microbiota culture, liver biopsy diagnosis of MASLD, and SIBO detected through intestinal permeability testing. The primary sources of heterogeneity are race and developed regions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=427040.